Low cost, high integrity plasmatron joining for automotive body in white manufacture - Dedenbach, Johannes (2016)
Plasmatron brazing is a unique tungsten inert gas (TIG) joining process, which allows joining of thin steel panels and is an economical alternative to laser brazing. This technology is used by some car manufacturers to generate water-tight joints on outer skin panels on low volume production lines. This study seeks to verify if Plasmatron brazing could be a new technique for high volume steel vehicle outer body skin joining, or if it would be better to concentrate on another technology. The current state of joining technologies in body production is presented. A rating of the most suitable joining techniques showed that laser and Plasmatron brazing are both ranked highly. Laser brazing is superior in terms of brazing speed but worse in regard to the capital investment cost. Plasmatron brazing is good in investment cost but drops in brazing speed and process feasibility due to the robustness of the electrode service life. As a by-product, the current limitations of the adhesive technology were delivered in detail. There is a need to make improvements to this technology. In a second part, a series of brazing experiments was undertaken to identify parameter influences and to improve the process window for Plasmatron joints. Findings indicate that a lateral filler wire – electrode tip misalignment of 0.3 mm resulted in marked base metal melting and unequal braze lines. Furthermore, strong evidence was found that brazing speed up to 2.5 m/min is possible only, with an energy input in the range between 74 - 84 Joule per mm. Current maximum braze speed is limited to 1 m/min. Moreover, it can be stated that the optimum joint quality can only be achieved through fine control of the input parameters and camera based control of the electrode tip settings. The last part investigated impact on post braze processes. For example, the behaviour of the electrode tip contamination and if it is possible to clean these electrodes. Furthermore, the influence of carbon deposits next to the braze seam to the following paint process was studied. Results show that the start stop phase during the brazing process is not associated with contamination's of the tungsten electrode tip. Also, it is possible to clean the electrode tip mechanically. Additional, carbon deposits next to braze seams must not be brushed away for the four tested zinc coat types before professional paint shop painting. Researchers can easily understand the overall developments and why focused arc brazing is a coming method for joining of automotive outer skin panels.